SEED PROTEIN PROFILING AND DIVERSITY ASSESSMENT OF LUPINUS ALBUS (L.) FROM AMHARA REGION, ETHIOPIA - Shiferaw, Eleni (Journal of Agricultural Sciences (Belgrade), 2022)
Seed protein profiling of 48 lupin accessions were evaluated to assess the genetic diversity of lupin from Amhara region, Ethiopia. A total of 30 bands were detected and used for the diversity assessment. The average number of bands, percentage of polymorphic bands and gene diversity among the analysed accessions were 16.96, 20.35 and 0.072 respectively. Diversity estimates analysed by grouping accessions based on their origin revealed that the highest diversity estimates were observed in Bahir Dar area followed by West Gojam and Agew Awi zones. Pair wise comparison of genetic distances (GD) among the analysed accessions ranged from 0.011 to 0.363. The most distantly related accessions were accession 6, collected from West Gojam and accession 28 from Bahir Dar area (GD = 0.378). Principal Coordinate Analysis (PCoA) showed absence of district group and most of the accessions were intermixed. Structure analysis revealed that the 48 lupin accessions could be assigned to three clusters. Most of the accessions from Agew Awi zone were grouped together while the rest of the accessions from different zones were grouped in the same cluster indicating that genotypes from the different zones had similar genetic background.